A ocupação e o uso das terras no sistema hidrográfico do rio Arauá Sergipe/Brasil: Histórico, dinâmica e espacialização - Bruna Leidiane Pereira Santana; Hélio Mario de Araújo (Confins)
The panorama of the spatial organization from the use and occupation of land allows to evidence the relationship between society and nature, prioritizing the dynamics of biophysical and socioeconomic aspects. This study aimed to analyze the evolution of land use and occupation in the Arauá River hydrographic system, from 2004 to 2014. The investigation was materialized methodologically with bibliographic survey, research and tabulation of secondary data, fieldwork and mapping of classes land use and occupation. In order to understand the current configuration of the landscape in relation to economic activities, there is a historic of occupation, linked to social aspects and edaphoclimatic characteristics. The scenario established with these stages shows a pattern of changes in the rural space, due to agricultural activities associated with the advancement of the technological level used in soil management and the genetic improvement of seeds used in agriculture. The main changes in land use occurred with the expansion of corn and pineapple crops, which have an evolutionary trend in the State of Sergipe. In the Arauá River hydrographic system, traditional temporary crops such as corn and beans, as well as citrus, in the period in evidence, show a decline in the quantity of production and in the planted area. In addition to the insertion of new types of crops, the advance of agricultural and pasture areas over fragments of native vegetation is identified, which accounts for only 6.6% of the territorial extension.